1999
DOI: 10.21836/pem19990507
|View full text |Cite
|
Sign up to set email alerts
|

Temporal production of nitric oxide and Prostaglandin E2 in media of explant cultures of equine synovial membrane and articular cartilage

Abstract: SummaryThe local mediators nitric oxide (NO) and prostaglandin E, (PGE ) play a role in the cascade of extracellular matrix breakdown in articular cartilage. In the present study the spontaneous production of NO and PGE, in explant cultures of equine synovial membrane and articular cartilage and their concentration over tjme n culture was investigated and correlated. Synovial membrane and articular cartilage was harvested from metacarpophalangeal jonts of 33 horses durlng arthroscopic surgery (n=4) or after be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2000
2000
2002
2002

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
3
2
0
Order By: Relevance
“…Interestingly, in experiment 2 in which SCL tissue was compared with synovial membrane and articular cartilage of equine joints with chip fractures, collagenolytic and gelatinolytic activities but not caseinolytic activity in SCL were very low. It may be that the high concentrations of NO and PGE2 in SCL inhibited the production of collagenase and gelatinase, confirming similar findings in our earlier study in which negative correlations between these local mediators and the production of NMPs were reported 21,24 …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Interestingly, in experiment 2 in which SCL tissue was compared with synovial membrane and articular cartilage of equine joints with chip fractures, collagenolytic and gelatinolytic activities but not caseinolytic activity in SCL were very low. It may be that the high concentrations of NO and PGE2 in SCL inhibited the production of collagenase and gelatinase, confirming similar findings in our earlier study in which negative correlations between these local mediators and the production of NMPs were reported 21,24 …”
Section: Discussionsupporting
confidence: 91%
“…Concentrations of NO, PGE2, and NMPs were often higher in SCL compared with joints with severe OA. This corresponded with our earlier findings in which joints affected with moderate OA generally produced higher concentrations of local mediators and matrix‐degrading enzymes compared with normal joints or joints with severe OA 24 . We speculated then that tissue from severe OA joints had lower cell numbers and viability.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These authors found that low concentrations of NO enhance PGE 2 , whereas high concentrations inhibit its synthesis. The same correlations between NO and PGE 2 concentration were found over 4 days in media of articular cartilage explant and synovial membrane cultures in other studies (von Rechenberg et al., 1998). In addition, in the same study a tendency for negative correlation's between NO and NMPs, and PGE 2 and NMPs was demonstrated.…”
Section: Discussionsupporting
confidence: 86%